Feasibility of a Broad Test Battery to Assess Physical Functioning Limitations of People Experiencing Homelessness - Broderick, Julie; Ni Cheallaigh, Cliona (My University, 2021)
Background: People who are homeless experience poor health. Reflective of overall health and factors such as acquired injuries, physical ability or functioning is often low among people who are homeless, but there is a lack of consistency of measures used to evaluate this construct. The aim of this study was to evaluate the feasibility of a broad test battery to evaluate limitations in physical functioning among people who are homeless. Methods: This cross-sectional, observational study occurred in a hospital in Dublin, Ireland. We evaluated lower extremity physical function (Short Physical Performance Battery), falls risk (timed up and go), functional capacity (six-minute walk test), stair-climbing ability (stair climb test), frailty (Clinical Frailty Scale), grip strength (handgrip dynamometer) and muscular mass (calf circumference measurement) in a population of people experiencing homelessness admitted for acute medical care. The test completion rate was evaluated for feasibility. Results: The completion rate varied: 65% (Short Physical Performance Battery), 55.4% (timed up and go), 38% (six-minute walk test), 31% (stair climb test), 97% (Clinical Frailty Scale), 75% (handgrip dynamometer), 74% (calf circumference measurement)). Collectively, the most common reasons for test non-participation were pain (24.1%, n = 40), not feeling well or able enough (20.1%, n = 33), and declined (11%, n = 18). Conclusion: The feasibility of the test battery was mixed as test participation rates varied from 31% to 97%. Physical functioning tests need to be carefully chosen for people who are homeless as many standard tests are unsuitable due to pain and poor physical ability.
PUBLISHED
Keywords: Homeless; Physical function; Frailty; Strength; Mobility; Inclusive Society; Mental Health/Psychosocial disability; Mobility impairment; Physical disability; Health